Prognostic value of preoperative albumin-to-alkaline phosphatase ratio in patients with surgically treated urological cancer: a systematic review and meta-analysis - Ren, Shangqing; Wang, Han; Yang, Bo; Zheng, Yang; Ou, Yong; Bao, Yige; Mao, Yu; Feng, Yunlin (Frontiers in Oncology, 2023)
Objective: A novel albumin-to-alkaline phosphatase ratio (AAPR) is associated with the prognosis of several cancers. In the present study, we evaluate the prognostic significance of perioperative AAPR in urological cancers. Method: Relevant studies were searched comprehensively from CNKI, PubMed, Embase and Web of Science up to March 2023. The pooled hazard ratio (HR) and 95% confidence interval (CI)were extracted from each study to evaluate the prognostic value of perioperative AAPR in patients with surgically treated urological cancers. Results: A total of 8 studies consisting of 3,271 patients were included in the final results. A low AAPR was significantly associated with a worse OS (HR=2.21; P<0.001), CSS (HR=2.61; P<0.001) and RFS/DFS (HR=2.87; P=0.001). Stratified by disease, a low AAPR was also associated with worse OS in renal cell carcinoma (HR=2.01; P<0.001), bladder cancer (HR=3.37; P<0.001) and upper tract urothelial carcinoma (HR=1.59; P=0.002). Conclusion: In conclusion, low AAPR could serve as an unfavorable factor in patients with surgically treated urological cancers. Stratified by tumor type, the low AAPR was also associated with inferior survival. While more prospective and large-scale studies are warranted to validate our findings.